Access to diagnostic tests during GP out-of-hours care: A cross-sectional study of all GP out-of-hours services in the Netherlands*. (2nd July 2016) - Schols, Angel M.R.; Stevens, Femke; Zeijen, Camiel G. I. P.; Dinant, Geert-Jan; van Vugt, Christel; Cals, Jochen W. L.
Abstract: Background: In general practice, excluding serious conditions is one of the cornerstones of the consultation. Diagnostic tests are widely used to assist the decision-making process in these cases. Little is known about general practitioners' (GPs) access to diagnostic tests at GP out-of-hours services. Objectives: To determine GPs' access to diagnostic tests—imaging, function tests, laboratory tests, and point-of-care tests (POCT)—during GP out-of-hours care and to assess whether access to diagnostic facilities differs between services located adjacent to or separate from an accident and emergency (A&E) department. Methods: Cross-sectional survey of all 117 GP out-of-hours services in the Netherlands in 2014. Results: One-hundred-seventeen GP out-of-hours services participated in the survey; response rate 100%. Access to diagnostic tests during GP out-of-hours care varied across services, although generally there was limited access. Electrocardiography was available in 26% (30/117) of all services, conventional radiography in 19% (22/117), laboratory tests between 37% (43/117) and 65% (76/117). All services had glucose POCT and urine dipstick tests available while none utilized troponin POCT. We observed no relevant differences in access to diagnostic tests between services adjacent to or separate from an A&E department. Conclusion: GPs in the Netherlands had limited and varying access to diagnostic tests during GP out-of-hours care in 2014. Out-of-hours services adjacent to A&E departments do not offer wider access to diagnostic tests. Further research on the accessibility of diagnostic tests in other European countries with similar and different GP out-of-hours care systems could shed further light on the effects of accessibility to diagnostic tests.